Health Equity in Dengue Prevention and Control: A Review of Social Vulnerability, Participation, and Climate-Related Risks - Sulistyawati Sulistyawati; Fatia Rizka Adela; Setiyo Harini; Septian Emma Dwi Jatmika (Universitas Ahmad Dahlan, 2026)
Background: Dengue remains a major public health problem in tropical and subtropical regions, with transmission and disease outcomes strongly influenced by social, economic, and environmental conditions. Evidence indicates that inequities in socioeconomic status, community participation, healthcare access, and climate vulnerability contribute to unequal dengue burden, yet these aspects are rarely synthesized comprehensively. Methods: This narrative review was conducted following the PRISMA guidelines. A literature search was performed using Google Scholar to identify original research articles published between 2020 and 2025 that explicitly addressed equity-related aspects of dengue prevention and control. Data were analyzed using narrative synthesis. Results: Six studies from Asia, the Caribbean, and Latin America were included. The findings showed consistent inequities related to socioeconomic status, geographic access to healthcare, community participation, financial protection, and climate-related vulnerability. Low-income and marginalized populations experienced poorer preventive practices, higher out-of-pocket healthcare costs, and greater exposure to dengue risk, while unequal institutional capacity limited the implementation of climate-based early warning systems. Conclusion: Dengue prevention and control are shaped by multidimensional inequities operating across social, community, and health system levels. An equity-oriented approach is needed to strengthen dengue control strategies, particularly through inclusive community engagement, improved healthcare access, and climate-informed public health interventions.